DETERMINING THE FACTORS THAT INFLUENCE THE MAGNITUDE OF LOSSES FROM EVAPORATION OF LIGHT HYDROCARBONS FROM GASOLINE IN HST - Бойченко, С. В.; Шутко, В. М.; Чернобаєва, Н. А. (Science-based technologies, 2014)
At present fuel supply value loss of petroleum products is determined by the ratio of quarterly petroleum product that has been accepted and the actual residue that is deposited. The difference between these values with realized amount is determined by natural losses. The object of research is the evaporation of gasoline during the execution of manufacturing operations. The subject of the research are the factors that affect the evaporation of gasoline in the SHT. The basis for the resolution of this issue could become operational information that may be collected by means of automation.